Strategies against Burnout and Anxiety in Medical Education - Implementation and Evaluation of a New Course on Relaxation Techniques (Relacs) for Medical Students - Wild, Katharina; Scholz, Michael; Ropohl, Axel; Bräuer, Lars; Paulsen, Friedrich; Burger, Pascal H. M. (PLoS ONE, 2014)
Burnout and stress-related mental disorders (depression, anxiety) occur in medical students and physicians with a significantly higher prevalence than in the general population. At the same time, the learning of coping mechanisms against stress is still not an integral part of medical education. In this pilot study we developed an elective course for learning relaxation techniques and examined the condition of the students before and after the course. 42 students participated in the semester courses in 2012 and 2013 as well as in a survey at the start and end of each course. The students were instructed in autogenic training (AT) and progressive muscle relaxation according to Jacobsen (PMR) with the goal of independent and regular exercising. At the beginning and the end of the semester/course the students were interviewed using standardized, validated questionnaires on burnout (BOSS-II) and anxiety (STAI-G), depression (BDI), quality of life (SF-12) and sense of coherence (SOC-L9). We compared the results of our students participating in Relacs with results from eight semester medical students (n = 88), assessed with the same questionnaires at similar points of time within their semester. Participating students showed a significant decline in cognitive and emotional burnout stress and in trait anxiety. Furthermore, they showed a reduction in state anxiety and a conspicuous decrease in mean depression. The sense of coherence increased at the same time. A comparative cohort of medical students of 8th semester students, showed lower values for the specified measurement parameters at the beginning, but showed no progressive changes. Our course introducing AT and PMR led to a significant reduction of burnout and anxiety within the participating group of medical students. Even the course attendance for just one semester resulted in significant improvements in the evaluated parameters in contrast to those students who did not attend the course.
EVALuna2:4405